2010
DOI: 10.1080/03630242.2010.506152
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Health Information-Seeking in Low-Income Pregnant Women

Abstract: The purpose of this study was to examine the relationships of health literacy, self-efficacy, and fetal health locus of control to health information-seeking in low-income pregnant women and the contribution from each factor alone or in combination to the variance in health information-seeking. This was a cross-sectional study of 143 English-speaking pregnant women who were recruited from a prenatal clinic and were 18 years of age or older in 2007-2008. Health literacy, self-efficacy, fetal health locus of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
0
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(100 citation statements)
references
References 44 publications
2
92
0
6
Order By: Relevance
“…The desire for information varies by patient and by circumstance. Demographic variables such as education level and race have been shown to influence information seeking (Rooks, Wiltshire, Elder, Belue, & Gary, 2012), as has health literacy (Shieh, Broome, & Stump, 2010). Patients with inadequate functional health literacy have worse comprehension of physician instructions and tend to ask fewer questions in the medical encounter (Sudore et al, 2009).…”
Section: B Gaglio Et Almentioning
confidence: 99%
“…The desire for information varies by patient and by circumstance. Demographic variables such as education level and race have been shown to influence information seeking (Rooks, Wiltshire, Elder, Belue, & Gary, 2012), as has health literacy (Shieh, Broome, & Stump, 2010). Patients with inadequate functional health literacy have worse comprehension of physician instructions and tend to ask fewer questions in the medical encounter (Sudore et al, 2009).…”
Section: B Gaglio Et Almentioning
confidence: 99%
“…In this study, health literacy was negatively correlated with FHLC-P. This means that women with low health literacy were more likely to believe that health professionals were responsible for their baby's health (21). In a prior study, the number of prenatal visits was found to be negatively correlated with internal maternal locus of control and positively correlated with external/ powerful others maternal locus of control among a sample of impoverished women.…”
Section: Is There a Relationship Between History Of Current Pregnancymentioning
confidence: 89%
“…Subsequent studies found that people with external beliefs take more risks during pregnancy, and pregnant women with internal beliefs are more likely to change their lifestyle and adopt positive health behaviors (15)(16)(17)(18)(19)(20)(21)(22). However, their number is few and no study conducted in Turkish society had been encountered.…”
Section: Introductionmentioning
confidence: 99%
“…In order to answer research questions 1 and 2 on the levels of information-need and information-seeking, a descriptive analysis was done. Table 2 above, presents the levels of information-need and informationseeking were categorized as high (35-50), moderate/average (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) and Low (1-17). It was found out that majority of the pregnant women in the study area had moderate level of pregnancy information needs (58.3%) and information-seeking (52.2%).…”
Section: Resultsmentioning
confidence: 99%
“…It comprised of five sections: Section A -Demographic Data Inventory; Section B: Sources of Information on Antenatal Care -13 items; Section C: Information Seeking Needs -12 items; Section D: Perceived Problems Inhibiting Information Seeking Needs -10 items; Section E: Information Seeking Types -10 items. The levels of information-need and information-seeking were categorized as high (35-50), moderate/average (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) and Low (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Maximum attainable score was 50.…”
Section: Instrument For Data Collectionmentioning
confidence: 99%